The Impact of Covid-19 on Hotel Industry In Asian Countries - Agustina, Indriyani Tri; Yosintha, Rolisda (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
The spread of Covid-19 has led to a global problem in all aspects of life, including in the tourism sector that directly affects the hotel industry. Asia as a continent with many countries that rely most of their revenue on tourism suffers a severe blow. The purpose of this study was to investigate the impacts of the novel Covid-19 on the hotel industry in Asian countries. Through a descriptive qualitative method, the researchers collected data from journals, research reports, books, government documents, articles, and websites. In analyzing the data, the researchers make a comparison between the Asian continent and other continents such as Europe, America, Africa, and Australia by focusing on the hotel occupancy in those continents. The result shows that the rate of hotel occupancy in Asia dropped by 57% and 63,4 million employees lose their jobs. This condition is mainly caused by the travel ban regulation that is followed by the temporary closure of tourist destinations. The hotel industry in Asia has lost up to US$ 1.041 million due to massive booking cancellations, and employees in this industry are even more severely affected as they have no income to support their life.